1992
DOI: 10.1161/01.cir.85.3.1125
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial perfusion and glucose metabolism in experimental left bundle branch block.

Abstract: LBBB itself may reduce myocardial perfusion and glucose uptake in the septum because of impaired systolic thickening and augmented intramyocardial pressure in the septum; however, this is not necessarily related to septal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
1
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 26 publications
5
67
1
4
Order By: Relevance
“…1,2 Left bundlebranch block reduces myocardial perfusion in the septum because of impaired systolic thickening and augmented intramyocardial pressure in the septum. 24 The present findings also demonstrate an inhomogeneous perfusion pattern, with a reduced SLR of resting MBF. In line with data from Nowak et al 10 using SPECT, CRT was found to have a homogenizing effect on perfusion.…”
Section: Discussionsupporting
confidence: 71%
“…1,2 Left bundlebranch block reduces myocardial perfusion in the septum because of impaired systolic thickening and augmented intramyocardial pressure in the septum. 24 The present findings also demonstrate an inhomogeneous perfusion pattern, with a reduced SLR of resting MBF. In line with data from Nowak et al 10 using SPECT, CRT was found to have a homogenizing effect on perfusion.…”
Section: Discussionsupporting
confidence: 71%
“…As a consequence, diastolic septal wall stress increases [39]. However, in the present study MVO 2 and MBF tend to be lowest in the septal wall.…”
Section: Regional Mvo 2 and Mbf In Dcm Patients With And Without Lbbbcontrasting
confidence: 61%
“…Myocardial scintigraphical studies of isolated LBBB patients demonstrated perfusion defects in the septum without coronary artery disease. LBBB per se may reduce myocardial perfusion and glucose uptake in the septum, because the interventricular asynchrony associated with LBBB causes excess systolic thickening and augmented intramyocardial pressure in the septum 13) . In addition, in patients with right ventricular pacing, a high incidence of myocardial perfusion defects in the septum associated with pacing induced artificial LBBB has been reported 10)14) .…”
Section: Discussionmentioning
confidence: 99%